Plasma Membrane Calcium ATPase Regulates Stoichiometry of CD4+ T-Cell Compartments - Merino-Wong, Maylin; Niemeyer, Barbara A.; Alansary, Dalia (Frontiers in Immunology, 2021)
Immune responses involve mobilization of T cells within naïve and memory compartments. Tightly regulated Ca2+ levels are essential for balanced immune outcomes. How Ca2+ contributes to regulating compartment stoichiometry is unknown. Here, we show that plasma membrane Ca2+ ATPase 4 (PMCA4) is differentially expressed in human CD4+ T compartments yielding distinct store operated Ca2+ entry (SOCE) profiles. Modulation of PMCA4 yielded a more prominent increase of SOCE in memory than in naïve CD4+ T cell. Interestingly, downregulation of PMCA4 reduced the effector compartment fraction and led to accumulation of cells in the naïve compartment. In silico analysis and chromatin immunoprecipitation unraveled point towards Ying Yang 1 (YY1) as a transcription factor regulating PMCA4 expression. Analyses of PMCA and YY1 expression patterns following activation and of PMCA promoter activity following downregulation of YY1 highlight repressive role of YY1 on PMCA expression. Our findings show that under the transcriptional control by YY1, PMCA4 adapts Ca2+ levels to cellular requirements during effector and quiescent phases and thereby represent a potential target to intervene with the outcome of the immune response.